EFFECTS OF LUTEOLIN AND LUTEOLIN-7-METHYL ETHER ON ESTROUS CYCLE AND INSULIN LEVEL IN PCOS MICE (Journal of Universal Science Research, 2025)
Polycystic ovary syndrome (PCOS) is one of the most common reproductive and endocrine disorders, accompanied by metabolic disturbances such as insulin resistance, hyperandrogenism, and infertility. Despite the wide spectrum of clinical manifestations, the exact etiology of PCOS remains unclear and involves genetic, environmental, and hormonal factors. Current therapies (oral contraceptives, insulin sensitizers, letrozole) primarily target symptoms, but their long-term application is limited by side effects and insufficient efficacy. Therefore, the search for alternative therapeutic agents is of particular importance. Recent studies indicate that flavonoids, such as luteolin, may exert beneficial effects on glucose and lipid metabolism, hormone regulation, and ovarian function.